Chile : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The report gives details of the economic analysis for the implementation of Chile's inflation targeting framework. It reviews the current state of liquidity in the Chilean fixed-income markets and developments and impediments to the supply of corporate bonds to the market. The paper considers a number of microstructure issues, transparency in the Over-the-Counter (OTC) market, addresses the role of public debt in facilitating development of the financial markets, and discusses a potential debt management framework that would support the development of a liquid public debt market.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet